A Review Of Energy Harvesting In Localization For Wireless Sensor Node Tracking - Dziyauddin, Rudzidatul Akmam; Mohd Ismail, Mohd Ismifaizul; Ahmad, Robiah; Ahmad, Norulhusna; Ahmad, Noor Azurati; Abdul Hamid, Afifah Maheran (Institute of Electrical and Electronics Engineers Inc., 2021)
The localisation and positioning in Wireless Sensor Node (WSN) are prone to tracking loss because of battery depletion resulted from high power consumption. Considering this, Energy Harvesting (EH) is a significant factor to ensure the sustainability of WSN trackers. Therefore, the key objective of the paper is to review the existing EH approaches, specifically for WSN trackers. An overview of WSNs including the underlying wireless communication technologies is initially presented. We compared the communication range, data rates, power consumption and also the cost across wireless technologies used for WSN. This paper further discussed the localisation and positioning techniques using the Global Positioning System (GPS) and other types of sensors exploiting signal parameters like Received Signal Strength Indicator (RSSI) and Angle of Arrival (AoA). Subsequently, we reviewed the energy harvesting approaches in terms of power density, efficiency and also highlighted their advantages and disadvantages. The EH components such as energy storage and energy-combining circuit for active monitoring are presented as well. Finally, this paper outlined the key challenges and future regards EH for WSN.